History of Hadith Codification in the time of the Prophet, Sahabat, and Tabi’in in Maintaining the Authority of the Sunnah - Abdullasani; Alan Saputra; Misbah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Hadith is the second primary source of Islamic teachings after the Qur’an, playing a crucial role in explaining and complementing its guidance. This study discusses the history of the codification of Hadith from the time of Prophet Muhammad (peace be upon him), through the periods of the Companions and the Followers (Tabi’in). During the Prophet’s lifetime, Hadiths were not officially written down due to the concern that they might be mixed with the Qur’an, although some Companions, such as Abdullah ibn Amr ibn al-‘Ash, possessed personal written records known as as-Sahifah. After the Prophet’s passing, the Companions exercised great caution in transmitting Hadiths to preserve their authenticity. In the era of the Tabi’in, the collection and documentation of Hadiths began to develop both through memorization and writing, spreading across various regions of the Islamic world. The official codification of Hadith was initiated during the caliphate of Umar ibn Abdul Aziz, who commissioned Ibn Shihab az-Zuhri to systematically compile Hadiths. This effort marked a significant milestone in the history of Hadith compilation, which continued during the generation of the Followers of the Followers (Tabi’ al-Tabi’in) with the emergence of major works such as al-Muwaththa’ by Imam Malik. This study emphasizes that the codification of Hadith was a gradual and systematic process aimed at preserving the authenticity and continuity of the Prophet’s teachings across generations.